An analysis of the energy split for grinding coal/calcite mixture in a ball-and-race mill. (July 2016) - Xie, Weining; He, Yaqun; Ge, Zhenzhou; Shi, Fengnian; Yang, Yong; Li, Hong; Wang, Shuai; Li, Ke
Graphical abstract: Highlights: Analyses and comparison of the traditional model for the energy split factor. Interaction between components is embodied with specific energy. Energy-size reduction model to calculate energy of component in mixture grinding. Calcite increases grinding energy efficiency of SCAC in the mixture breakage. Abstract: Interactions among components in the heterogeneous grinding would change energy consumed characteristics of components if compared with those in the single-component breakage. In this paper, energy split phenomenon for the coarse grinding of super clean anthracite coal (SCAC)/calcite mixture of 2.8–2 mm in the ball-and-race mill is investigated. Before the analysis of experimental results, accuracy of energy split function in terms of time-dependent breakage rate is first discussed. Energy consumed characteristics of grinding in the ball mill and ball-and-race mill are also compared. Breakage model of product t10 (yield of progenies in −0.237 mm) vs specific energy is used to describe the energy-size reduction of the single-component and multi-component grinding. Interaction between components is reflected by the comparison of specific energy of components in mixture and single breakage to yield the same product t10 . Based on the energy balance, energy split factors of components in different time and mixed conditions are first determined. This parameter shows no change with time. Calcite increases the grinding efficiency of SCAC significantly, with the energy split factor for SCAC ranging from 0.68 to 0.73, which means less specific energy is consumed by SCAC to yield the same t10 if compared with the single breakage. As the volumetric ratio of calcite increases in mixture, grinding energy efficiency decreases and energy split factor of calcite increases from 1.70 to 1.83. Soft material reduces the grinding energy efficiency of hard one in the multi-component breakage.